Surveillance of Newcastle disease virus in wild birds at Albufera de Medio Mundo lagoon - Mendoza R., Luis (2012)
The study evaluated the presence of the Newcastle disease virus in the Albufera de Medio Mundo lagoon, situated north of Lima. The lagoon is inhabited for various wild migrant bird species. Three sampling periods were conducted of six weeks each, colleting 900 fresh fecal samples from 11 species. Samples were inoculated in specific-pathogen free (SPF) embryonated eggs of 10 days of age for isolation of the virus. The hemagglutinant activity of the allantoic fluid showed negative results in all samples. The estimated prevalence calculated through a beta simulation was 0.1% with a distribution between 0.002 and 0.4%. The prevalence was too low for considering these birds as a possible source of infection toward domestic birds.